Pharmacology of TNF blockade in rheumatoid arthritis and other chronic inflammatory diseases. - Taylor, P (2010)
Tumor necrosis factor-alpha (TNF) has been unequivocally validated as a therapeutic target in a number of immune-mediated inflammatory disorders (IMIDs). There is now increasing choice of biologic agents within the class all of which successfully neutralize sTNF. But approaches to TNF inhibition differ and currently include mAbs (infliximab, adalimumab, and golimumab), either chimeric or human in sequence, a PEGylated Fab' fragment (certolizumab), and an IgG1-TNFR2 fusion protein (etanercept). It is emerging that the pharmacological properties of these three anti-TNF subtypes differ with respect to Fc function, binding of tmTNF and the possible consequences of this, as well as the ability to form complexes. The mode of administration of each agent, clearance and the local tissue concentrations achieved may also confer unique characteristics of relevance with respect to efficacy and safety.